Resilience of Entrepreneurial Activity: GEM Slovenia 2021, Executive Summary (University of Maribor Press, 2022)
The GEM survey provides a deeper insight into national entrepreneurship and its characteristics than can be provided by other statistical sources, especially those based solely on data obtained from existing enterprises. With the individual at the heart of the research, GEM also covers his attitude towards entrepreneurship, his ambitions and qualifications for entrepreneurship, his perception of society’s attitude towards entrepreneurship, as well as individuals at all stages of the entrepreneurial process, until the establishment of the company, business growth and termination of business. GEM’s research ambition is to measure key elements of society’s attitudes towards entrepreneurship, entrepreneurial activity and differences in individuals’ aspirations in as many countries as possible, and to identify influential factors that encourage or hinder entrepreneurial activity. All this in order to provide a platform for assessing the impact of entrepreneurial activity on economic growth and to identify policy measures to strengthen entrepreneurship. GEM has developed an appropriate methodology that is consistent with the GEM conceptual framework and is able to provide insight into the social, cultural, political and economic context, taking into account the level of development of each national economy and the development of key business conditions.